The Lethality of Female Suicide Bombers - Fullmer, Nyssa (Women & criminal justice, 2019)
Over the past 50 years, suicide bombings have become an increasingly common tactic of politically motivated violence, and a rising number of these attacks feature women perpetrators. Prior literature suggested that female-perpetrated suicide bombings occurring between 1985 through 2008 inflicted greater casualties, which may account in part for their increased use by terror groups. The current research project ascertains whether sex continues to predict the lethality of suicide bombing attacks perpetrated by terror groups over the decade leading up to 2016. The study utilizes secondary data sampled from the Global Terrorism Database (N = 881) and the Chicago Project on Security and Threats (N = 1,722). A negative binomial model regressing lethality against perpetrator and conflict covariates did not observe a statistically significant relationship between sex and lethality. Male and female suicide bombers demonstrated similar lethality in suicide bombing events between 2005 and 2016, although scatterplots suggest some aberration during the years 2009, 2010, and 2016. Pairwise comparisons of perpetrator sex by conflict observed some variation in the lethality of attacks, with female suicide bombers from Al Qaeda, the Islamic State of Iraq, and Iraqi rebel groups found more lethal than male suicide bombers from Boko Haram and the Nigerian rebels. The current research project contributes to the literature by demonstrating the evolving nature of terrorism and tactics relevant to the lethality of politically motivated violent attacks.